Ars et methodus: Philipp Melanchthon's humanist concept of philosophy - Bihlmaier, Sandra (Refo500 academic studies, 2018)
Angaben zur beteiligten Person Bihlmaier: After defending her doctoral thesis in philosophy in the spring of 2017, Dr. phil. Sandra Bihlmaier decided to explore new branches of knowledge. She is currently working in the field of automotive technology in the Stuttgart area.